2013
DOI: 10.1186/1749-8090-8-81
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve reoperation under ventricular fibrillation through right mini-thoracotomy using three-dimensional videoscope

Abstract: BackgroundConventional reoperative mitral valve surgery by median sternotomy has several difficulties. We performed mitral valve replacement (MVR) under ventricular fibrillation (VF) through right mini-thoracotomy with three-dimensional videoscope for avoiding the problems.MethodsBetween 2006 and 2011, we performed 257 cases of MVR, in which 125 cases underwent isolated MVR. Ten cases of patients underwent reoperative MVR under VF through thoracotomy with three-dimensional videoscope (Group I), and 27 cases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 17 publications
3
21
1
Order By: Relevance
“…A recent study by Romano showed that the beating-heart technique is as safe as the arrested-heart technique, with less blood transfusion and lower ventilator times (22). Hiraoka et al performed 10 cases of re-MVR under VF by thoracotomy with a threedimensional videoscope in 2013, and their early experience suggested that the procedure was acceptable as an effective alternative (23). Results of our study confirmed this conclusion.…”
Section: Discussionsupporting
confidence: 82%
“…A recent study by Romano showed that the beating-heart technique is as safe as the arrested-heart technique, with less blood transfusion and lower ventilator times (22). Hiraoka et al performed 10 cases of re-MVR under VF by thoracotomy with a threedimensional videoscope in 2013, and their early experience suggested that the procedure was acceptable as an effective alternative (23). Results of our study confirmed this conclusion.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, the rates for freedom from stroke events and reoperation for bleeding were nearly 0%. In addition, 3 other retrospective observational studies all demonstrated the superiority of an RT approach as compared to a median sternotomy for reoperative mitral valve surgery, with excellent results noted in those cases (Table 5) [16][17][18]. Pooled analysis showed a mini-thoracotomy mitral valve surgery procedure as a safe alternative to a standard sternotomy, with reduced mortality rates, length of hospital stay, and reoperations for bleeding, along with a comparable risk of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…However, we as well as others have reported mitral valve replacement or repair under ventricular fibrillation or even on a beating heart. 5 We therefore decided to go for femoral cannulation and to perform the surgery under ventricular fibrillation.…”
Section: Discussionmentioning
confidence: 99%